Pseudomyogenic Hemangioendothelioma Mimicking Multiple Myeloma on 18F-FDG PET/CT, Followed by Spontaneous Regression. (July 2015) - Bryanton, Mark; Makis, William
Abstract : Abstract: Pseudomyogenic (epithelioid sarcoma-like) hemangioendothelioma is a rare, recently described vascular neoplasm that occurs predominantly in the distal extremities of young to middle aged adult males. In this report, we describe a patient who presented with numerous lytic bone lesions which were intensely 18 F-FDG avid on PET/CT and presumed to be metastatic. Pathology revealed pseudomyogenic hemangioendothelioma. Follow-up CT showed enlargement and increasing sclerosis of several lesions, believed to represent progression; however, follow-up PET/CT confirmed a spontaneous regression of the disease.